NEURONAL SYNCHRONIZATION AND ARTIFICIAL INTELLIGENCE: PROSPECTS FOR EARLY DETECTION OF THREATS TO LOVED ONES (Uzbekistan Open Conference, 2025)
The article explores the phenomenon of neural synchronization between emotionally connected individuals and the potential for predicting such states using modern technologies. It examines the mechanisms of synchronized brain and physiological activity that may underlie the intuitive sense of connection between partners, friends, and family members. The potential of artificial intelligence and biometric systems for early detection of emotional and physiological changes is analyzed. The paper highlights the prospects of developing “predictive empathy” technologies and emphasizes the importance of ethical considerations in their application.